2023
DOI: 10.3390/insects14010054
|View full text |Cite
|
Sign up to set email alerts
|

A New Pest Detection Method Based on Improved YOLOv5m

Abstract: Pest detection in plants is essential for ensuring high productivity. Convolutional neural networks (CNN)-based deep learning advancements recently have made it possible for researchers to increase object detection accuracy. In this study, pest detection in plants with higher accuracy is proposed by an improved YOLOv5m-based method. First, the SWin Transformer (SWinTR) and Transformer (C3TR) mechanisms are introduced into the YOLOv5m network so that they can capture more global features and can increase the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Specifically, YOLOv5 models excelled in localizing lesions within frames, with the YOLOv5m model performing the best with an mAP@0.5 of 0.92 and mAP@0.5:0.95::0.05 of 0.48. It strikes a balance between speed and accuracy, making it suitable for real-time applications where both these factors are crucial, as seen in [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, YOLOv5 models excelled in localizing lesions within frames, with the YOLOv5m model performing the best with an mAP@0.5 of 0.92 and mAP@0.5:0.95::0.05 of 0.48. It strikes a balance between speed and accuracy, making it suitable for real-time applications where both these factors are crucial, as seen in [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our technique is effective in performance and report measurements. Drawing upon an extensive review of relevant academic literature, a majority of the research conducted on images [28][29][30][31][32][33][34][35][36][37][38][39]50] indicates a lack of sufficient attention towards the establishment of reliable analytical techniques for prevention and control [40][41][42][43][44][45] and accurately identifying pests through the analysis of acoustic signals produced by these pests [46][47][48][49]. The summarized findings of these reviews can be found in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teng et al 6 proposed a combination of multi-scale super-resolution feature enhancement module named MSR and multi-location detection module named SI to detect 26 common pests, which improved the accuracy to 67.4%. Dai et al 7 proposed to introduce SWinTR and C3TR mechanisms into the YOLOv5m network to capture more global features and increase the receiving domain of image features. Finally, the detection accuracy of 10 common insect pests, such as vertical rice leaf rollers and vertical rice leaf rollers, was achieved at 95.7%.…”
Section: Introductionmentioning
confidence: 99%